2012
DOI: 10.1128/aem.00715-12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR for Tracking the Megaplasmid-Borne Biodegradation Potential of a Model Sphingomonad

Abstract: ABSTRACTWe developed a quantitative PCR method for tracking thedxnA1gene, the initial, megaplasmid-borne gene inSphingomonas wittichiiRW1's dibenzo-p-dioxin degradation pathway. We used this method on complex environmental samples and report on growth ofS. wittichiiRW1 in landfill leacha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The chromids and/or megaplasmids whose copy numbers have been examined in the family Rhizobiaceae (48)(49)(50) and the genera Burkholderia (51) have a copy number approximately equal to that of the chromosome. Similarly, the copy numbers of the large plasmids of Thermus thermophilus (52) and Sphingomonas wittichii (53) are similar to those of the chromosomes. However, the copy number of the chromid of the fast-replicating organism V. cholerae can actually be lower than that of the chromosome depending on the growth medium (54).…”
Section: Replication and Segregation Dynamics In Multipartite Genomesmentioning
confidence: 70%
“…The chromids and/or megaplasmids whose copy numbers have been examined in the family Rhizobiaceae (48)(49)(50) and the genera Burkholderia (51) have a copy number approximately equal to that of the chromosome. Similarly, the copy numbers of the large plasmids of Thermus thermophilus (52) and Sphingomonas wittichii (53) are similar to those of the chromosomes. However, the copy number of the chromid of the fast-replicating organism V. cholerae can actually be lower than that of the chromosome depending on the growth medium (54).…”
Section: Replication and Segregation Dynamics In Multipartite Genomesmentioning
confidence: 70%
“…When utilizing S. wittichii RW1 as a bioremediation agent, it may be possible to induce the expression of the dioxin degradation pathway using acetate. Induction of the dioxin degradation pathway has not been observed when S. wittichii RW1 is grown on glucose or rich medium [ 22 ], and growth in a complex environmental medium (landfill leachate) was correlated with a decrease in copy number of the gene encoding the dioxin dioxygenase alpha subunit [ 37 ]. Previous studies using S. wittichii RW1 to transform chlorinated dioxins in soil or fly ash have observed a progressive decrease in degradative activity [ 5 ] or viable cells [ 38 , 39 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A number of PCR primers are reported that can be used to probe samples for aromatic ring-hydroxylating dioxygenase genes (ARDHs) (Iwai et al, 2011b), including a quantitative PCR primer specific to the dxnA1 in Sphingomonas wittichii str. RW1, which is the only well-characterized dioxin degrader (Hartmann et al, 2012). However, no previously published primer set meeting the requirements for amplicon sequencing solely targets dioxygenases active toward dioxins (Iwai et al, 2011b).…”
Section: Aromatic Hydrocarbon-degrading Dxna Dbfa1 and Caraa Genesmentioning
confidence: 99%